ABOUT REQUIREMENTS FOR EXACTNESS OF METEOINFORMATION - M. B. Fridzon; О. A. Еvtushenko (Научный вестник МГТУ ГА, 2016)
Appraisement of requirements for initial information for example of downpour precipitation’s prognosis is conducted. The problem of rational place for network of automatical stations on watch - towers of comb communication is considered.